Little MONSTER TRUCKS - Cenko, Doug (Cincinnati, Ohio : Blue manatee Press, 2020)
Little monster trucks are met with challenge after challenge and must find a way to stay on the road and finish the race! Will they all make it, and who will win?
Keywords: English fiction; Monster trucks -- Juvenile fiction; Picture books